Methyl-α-d-glucopyranoside as Green Ligand for Selective Copper-Catalyzed N-Arylation - Chen, Yuanguang; Du, Fangyu; Chen, Fengyang; Zhou, Qifan; Chen, Guoliang (Synthesis, 2019)
In the selective N-arylation of amines or azoles with aryl halides, methyl-α-d-glucopyranoside (MG) was found to function as a green ligand of copper powder. In addition, nitrogen heterocyclic amine compounds can also undergo the N-arylation coupling with heterocyclic aryl chlorides. This process allows access to a variety of aromatic amines and aryl azoles under mild reaction conditions, has good tolerance, and proceeds in moderate to high yield.
Keywords: N-arylation; ligands; catalysts; nitrogen heterocycles; azoles